A rare agent of empyema: Gemella morbillorum: Rare agent of empyema - Özpınar, Selin Beyza; Mutlu, Pınar (Journal of Surgery and Medicine, 2025)
Gemella morbillorum is a pathogen that rarely causes pleural infections. This case report presents an 80-year-old male patient diagnosed with empyema, in whom Gemella morbillorum was identified in the pleural fluid culture. This case highlights the importance of considering rare pathogens in pleural infections and how pleural fluid cultures can aid in accurate diagnosis and treatment.